Harga Transfer, Kesulitan Keuangan, Manajemen Laba, dan Penghindaran Pajak: Ukuran Perusahaan sebagai Pemoderasi - Suyanto; Sari Apriliyana; Hani Alfiani; Fuadhillah Putri (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to examine transfer pricing, financial distress, earning management toward tax avoidance with firm size as moderating variable. The sample used in this study are companies of all sectors listed on the Indonesia Stock Exchange (IDX) in 2016-2019 and generated 171 sample data from 81 companies. The data analysis used in this research was conducted by using regression analysis and interaction test. The results indicate that transfer pricing has negative effect on tax avoidance, financial distress has negative effect on tax avoidance, earnings management has no effect on tax avoidance, firm size is unable to moderate the effect of transfer prices on tax avoidance, firm size is unable to moderate the effect of financial distress on tax avoidance and firm size are unable to moderate the effect of earnings management on tax avoidance.